On the Verge of Institutionalisation? Participatory Budgeting Evidence in Five Italian Regions - Allegretti, Giovanni (2021)
Over the past few years, Italy has been setting the stage for different democratic innovations, especially those that have been implemented at municipal (or sub-municipal) level in different parts of the country. The expansion of Participatory Budgeting has been a remarkable one, accompanied by the diffusion of regional laws that were adopted to promote a culture of more intense civic participation. Moving from an overview of the recent diffusion of Participatory Budgeting in different areas of the country, this article proposes a reflection on what kind of added value the existence of this legal provision has led to the promotion of participation at a regional level and what this may represent. The construction of the Italian branch of Participatory Budgeting’s World Atlas offers an opportunity to assess legal provisions’ contribution to the diffusion and enrootment of participatory practices, especially in smaller-scale municipalities. Through zooming into some cases (such as Sicily, Emilia Romagna, Apulia and Tuscany, or Lazio in the last few years) the authors argue that the formalisation of participatory practices into legal frameworks today is an important but not a sufficient factor that diffuses and enroots participatory culture in local territories, and that a supplement of monitoring structures and detailed studies would help make challenges and added values of regional law frameworks clearer.